Kawin Sirri dan Pancasila: Analisis Keselarasan dengan Prinsip-prinsip Konstitusi Indonesia : Sirri Marriage and Pancasila: Analysis of Alignment with the Principles of the Indonesian Constitution - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Muhtarom Adnan Al Kahfi; Muhammad Haidar Ali Yahya; Akhsan Khoirul Anam (Litera Academica Publishing, 2025)
Pancasila, as the foundation of the state and ideology of the Indonesian nation, plays a crucial role in the formulation of legal policies, including in counter-terrorism efforts. This article discusses how Pancasila values, such as justice, humanity, and unity, are integrated in Indonesia's anti-terrorism legal policy. Pancasila provides a philosophical foundation that ensures the policy is not only effective in maintaining national security, but also respects human rights, prevents discrimination, and strengthens national unity. Thus, the anti-terrorism policy prepared based on Pancasila is expected to realize law enforcement that is just, humanity-based, and supports the integrity of the Indonesian nation. The research method used is the Normative Juridical Approach method, this method focuses on the study of literature and legal regulations, such as the Anti-Terrorism Law in Indonesia. Researchers usually analyze statutory documents, legal theories, and how Pancasila values are applied in existing legal policies. The results of this study reveal that the role of Pancasila in making anti-terrorism legal policy in Indonesia shows that the philosophical idiological values of Pancasila serve as the foundation for the policy).